Digital Learning Training for PKBM 31 Bangka Educators for Classroom Transformation After the Covid-19 Pandemic - Wahyuningdiah Trisari H Putri*; Muhammad Darwis; Retno Hendrowati; Quintin Kurnia Dikara Barcah; Tri Wahyuti; Elza Dwi Juniar; Rayhan Alsauqi (Universitas Lancang Kuning, 2023)
Digital learning is a form of transformation in the classroom that focuses on the use of technology. In Indonesia, the Covid-19 pandemic that has been going on for the last few years has forced educational institutions, both formal and non-formal, to apply this learning concept, even with all of its limitations. This is at least experienced by PKBM 31 Bangka which has attempted to implement digital learning with limited capabilities and minimal infrastructure. This is even worse with the diverse characteristics of the students as non-formal institutions. Therefore, through a community service program, the informatics engineering study program at Paramadina University seeks to provide training to PKBM 31 Bangka so that they are better prepared to carry out digital learning. The training was held for 2 days and divided into 4 sessions. The understanding and ability of PKBM 31 Bangka educators regarding digital learning increased from the previous 2.67 to 4.25 after attending the training. Participants also rated the implementation of this training at 4.5 or very satisfied.